Bioremediation through microbes: systems biology and metabolic engineering approach. (2nd January 2019) - Dangi, Arun Kumar; Sharma, Babita; Hill, Russell T.; Shukla, Pratyoosh
Abstract: Today, environmental pollution is a serious problem, and bioremediation can play an important role in cleaning contaminated sites. Remediation strategies, such as chemical and physical approaches, are not enough to mitigate pollution problems because of the continuous generation of novel recalcitrant pollutants due to anthropogenic activities. Bioremediation using microbes is an eco-friendly and socially acceptable alternative to conventional remediation approaches. Many microbes with a bioremediation potential have been isolated and characterized but, in many cases, cannot completely degrade the targeted pollutant or are ineffective in situations with mixed wastes. This review envisages advances in systems biology (SB), which enables the analysis of microbial behavior at a community level under different environmental stresses. By applying a SB approach, crucial preliminary information can be obtained for metabolic engineering (ME) of microbes for their enhanced bioremediation capabilities. This review also highlights the integrated SB and ME tools and techniques for bioremediation purposes.